Experience of development of porphyry copper type deposits in the Urals - I. A. Altushkin; V. V. Levin; A. V. Sizikov; Yu. A. Korol' (Записки Горного института, 2017)
Russian copper company was the first in Russia to start developing porphyry copper deposits. In 2013 the Mikheevsky mining and processing plant with the annual production capacity of 18 mln t of ore was put into exploitation. The use of innovative approaches regarding choice of the technology, high-performance equipment and organization of construction allowed to bring the enterprise to a full capacity and to achieve expected results within three years. On the basis of the experience obtained during design, construction and exploitation of the Mikheevsky mining and processing plant in 2017 the company has started the construction of a new mining and processing plant in the Tominskoye deposit. The first stage anticipates the enterprise production capacity to be equal to 28 mln t with the possibility of its increase up to 56 mln t. The development of porphyry copper deposits in the Urals will allow to provide copper plants with the raw materials over the next 80-100 years.